Navigating autonomy: unraveling the dual influence of job autonomy on workplace well-being in the gig economy - Wan, Zhitao; Zhang, Lei; Wang, Li; Zhang, Fang (Frontiers in Psychology, 2024)
Introduction With the rapid rise of the gig economy globally, its characteristics of promoting employment and facilitating autonomy have supported its rapid growth and development in China. While the flexibility of gig work offers more employment options and income sources for workers, it also caused many problems and uncertainties. Workplace well-being is an important psychological factor that indicates the psychological state of workers and significantly predicts their behavior at work. However, previous studies on the gig economy rarely analyze gig workers’ workplace well-being, which is of great significance to improving their individual emotions, promoting their physical and mental health, and maintaining the sustainable development of the gig economy and society in general. Methods This study draws on the cognitive-affective processing system framework to construct a moderated dual-mediator model to explore the dual influence mechanism of job autonomy on gig workers’ workplace well-being. Based on the data of 442 digital gig workers who were mainly engaged in manual labor. Results The survey results show that job autonomy positively affects employees’ workplace well-being, and work alienation and positive emotion mediate this relationship. Perceived algorithmic control can moderate not only the influence of job autonomy on work alienation and positive emotion but also the indirect impact of job autonomy on workplace well-being through work alienation and positive emotion. Discussion The finding of this research contributes to expand the comprehension of the relationship between gig-worker job autonomy and workplace wellbeing and this relationship’s underlying mechanism, holding significant implications for management practice.